Automated mapping of K-feldspar by electron backscatter diffraction (EBSD) and application to 40Ar/39Ar dating - McLaren, S.; Reddy, Steven (Pergamon-Elsevier Science Ltd., 2008)
The ability to quantify feldspar microstructure using the electron backscatter diffraction (EBSD) method has direct application in the study of rock deformation and strain kinematics. However, automated EBSD analysis of low symmetry phases, such as feldspar, has previously proven difficult. Here, we successfully apply the EBSD method to a number of granitic feldspars and develop automated phase and orientation mapping to discriminate K-feldspar and plagioclase, and quantify orientation variations within individual K-feldspar grains. These results represent the first automated quantitative mapping of orientation microstructure in K-feldspar. We use the method to evaluate the relationship between microstructure and 40Ar/39Ar age, a controversial problem in thermochronology. In a granitic K-feldspar from central Australia, the range of observed orientation domains matches the small-intermediate and largest domain sizes predicted from multiple-diffusion domain modelling. In situ ultra-violet laser microprobe analyses show that the youngest ages from the 40Ar/39Ar age spectra are recorded by grain mosaic K-feldspars with diameter around 10-50 m. These K-feldspars are the smallest coherent microstructural features observed on scales of > 1 m. Large 250-1000 m diameter microstructurally simple grains record the oldest ages observed in the age spectrum. These results suggest a first order relationship between K-feldspar microstructure and 40Ar/39Ar age and demonstrate a microstructural control on multidomain diffusion.